Hypholoma himalayense, a new and noteworthy species from the Himalayan moist temperate forests of Pakistan - Ayyub, Misbah; Niazi, Abdul Rehman (Phytotaxa, 2023)
Hypholoma himalayense, a new species is described and illustrated from the Himalayan moist temperate forests of Pakistan. This new taxon can be differentiated from close allies by its reddish-orange to light orange pileus, light yellowish to dull brown lamellae, and larger and broader basidiospores. The new species is also supported by molecular phylogenetic analysis inferred from the internal transcribed spacer (ITS) region.